Implementation of Thoharoh in early childhood through Telling Story in Babadan Village - Lilis Rahmawati (STAI Miftahul Ula Nganjuk, 2020)
Thoharoh became the basis of a practice of worship, as it became the condition of worship. So it is necessary to be taught since early childhood is good and correct. Since early childhood is the Golden Age. This research aims to discuss the implementation of education in Thoharoh in early childhood in Babadan village. Using a descriptive method is a clear picture of delivering, presenting, and concluding data. Population retrieval and samples from the research object as a tool to obtain data from an issue that is also required by the authors. As for digging data, the methods used are documentation methods, interviews, polls and to know the type of data using qualitative data. His study was done very impressively through various fun games, demonstrations and Thoharoh festivals. The results showed that Thoharoh could be implemented early on through a pleasant method. With the hope that parents participate in this religious education so that the child can practice it optimally.